A Comparative Study Of Continuing Professional Development For Speech Therapists And Teachers In Armenia And Beyond - Kalfayan, Ashekian Taline
The objective of this research project is to present a comprehensive examination of the disparities in continuous professional development (CPD) for speech therapists and teachers. The consequences for service quality and professional standards within these two critical disciplines will be the primary focus of the analysis. As mandated by the regulatory framework, teachers in Armenia, for example, must participate in continuing professional development (CPD) programs to maintain their professional qualifications. On the other hand, speech therapists are not subject to the same responsibilities, which causes significant differences between the two professions in terms of the development of skills and the ongoing of their education. This study compares the consequences of several continuing professional development requirements, shared professional practices, and relevant government laws. A critical analysis of the quantitative and qualitative pros and cons of mandating continuing professional development (CPD) for speech therapists is conducted. To support this review, empirical evidence has been gathered via interviews with important stakeholders and a comprehensive study of the present accessible knowledge. These findings highlight the urgent need for a more organized and coherent continuous professional development (CPD) framework particularly designed for speech therapists, that conforms with the professional development policies set for teachers, and that is more consistent. Additionally, this research offers specific recommendations that are designed to enhance legislative structures to increase the opportunities for continuing professional development (CPD) in both professions. The suggested projects are meant to improve the quality of services and professional knowledge in speech therapy as well as to guarantee that every professional working in Armenian educational and therapeutic environments satisfies high criteria of competence. The communities they serve will eventually gain from this. This will be achieved by fostering a culture of ongoing professional development.
Keywords: Speech therapy